2016
DOI: 10.1007/s40675-016-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Circadian Rhythms, and Fertility

Abstract: Adequate sleep is crucial for general health and wellbeing. Although the neuronal control of the reproductive axis and sleep-generating neurons share an anatomical location, little is known regarding the impact of sleep and circadian disruption on fertility in women. Animal models have established clear circadian control of the pre-ovulatory luteinizing hormone surge. Additionally, disruption of the circadian timing system by exposure to abnormal light-dark cycles or mutations of core clock genes results in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 130 publications
(186 reference statements)
1
17
0
Order By: Relevance
“…High levels of melatonin are found in human ovarian follicular fluid secreted by the pineal gland and ovaries. During ovulation, the importance of melatonin present in the ovarian follicles is to protect the oocyte from oxidative stress [95]. In a study, low levels of follicular melatonin were observed to be associated with higher levels of reactive oxygen species (ROS) and reduced oocyte quality in infertile women [96].…”
Section: The Effects Of Melatonin On Reproductive Healthmentioning
confidence: 99%
“…High levels of melatonin are found in human ovarian follicular fluid secreted by the pineal gland and ovaries. During ovulation, the importance of melatonin present in the ovarian follicles is to protect the oocyte from oxidative stress [95]. In a study, low levels of follicular melatonin were observed to be associated with higher levels of reactive oxygen species (ROS) and reduced oocyte quality in infertile women [96].…”
Section: The Effects Of Melatonin On Reproductive Healthmentioning
confidence: 99%
“…SD has serious adverse effects on different body functions resulting in cardiovascular diseases, immune disturbances and neuro-endocrinal changes [9]. Furthermore, SD and psychological stress alter the activity of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system with negative impact on both sexuality and fertility [10]. Inadequate sleep has been reported to decrease semen quality [11].…”
Section: Introductionmentioning
confidence: 99%
“…PPARs are essential for trophoblast invasion, decidualization, tissue remodeling, ovarian function, and placental formation ( 134 – 136 ). Additionally, circadian rhythm disturbance is reported to affect female fertility ( 137 ). Rev-erb is a circadian NR, which maintains the circadian rhythm ( 138 ) and may have a role in female fertility.…”
Section: Nrs and Fgtb: Potential Markers And Drug Targetsmentioning
confidence: 99%